A Rapid and Satisfactory Outcome with Combined Immunosuppressive Therapy in Acquired Haemophilia A with Underlying Tuberculosis. (29th November 2022) - Gamakaranage, G. A. C.; Kulathilake, C.; Nadeeshani, P. G. N.; Fernandopulle, K. H. B. P.; Moonesinghe, C. S.; Gunawardena, D.; Gamage, R. S.; Perera, N.; Indrakumar, J.
Abstract : Acquired haemophilia A (AHA) is a rare disorder with an incidence of 1.5 cases per million per year in the United Kingdom. The incidence could be underestimated due to difficulty in diagnosis and also due to the fact that people with low titre inhibitor levels are asymptomatic. It is usually a disease affecting elderly but a disease peak in the younger population is known. The common underlying diseases are autoimmune disorders, malignancies, infections, and drugs. However, approximately 50% of the cases do not have a specific aetiology and about 10% will not have bleeding manifestations. Therefore, an isolated prolongation of APTT should be evaluated, especially prior to any haemostatic challenges. We report a case of a middle-aged man who presented with bleeding due to AHA associated with high inhibitory titres and active pulmonary tuberculosis. He was treated with both antituberculous and combined-aggressive immunosuppressive therapy which resulted in satisfactory disease remission.